KAJIAN DAMPAK SUBSTITUSI KACANG TUNGGAK PADA KUALITAS FISIK DAN KIMIA TAHU - Rosida, Dedin F; Hardiyanti, Qomariyah; Murtiningsih, Ir (UPN VETERAN JAWA TIMUR, 2011)
Tofu is a soy protein product with a protein coagulation process at its soelektric point. Soy protein precipitation was range between pH 4.5 which is the point isoelektris soybean globulin. In efforts to reduce the use of soy in the making tofu, cowpea is one source of vegetable protein had a good nutritional composition of one protein, vitamain B, vitamin C and fiber. Cowpea can be used as raw material of tofu. The use of citric acid as a coagulant will give a high yield in tofu. This study aims to know the effect of the proportion of cowpea and citric acid concentration on the quality of physical, chemical and organoleptic while they knew the best treatment combination.This research used Completely Randomized Design (CRD) which are arranged in factorial which consist of two factors and repeated 3 times. Factor I is the proportion of cowpea 20%, 30%, 40% and the second factor is the concentration of citric acid solution is 10.5%, 11.5%, 12.5%.The best results are obtained on the proportion of 20% cowpea treatment with citric acid concentration of 12.5%.The resulting was in a yield of 158.767%, moisture content of 80.131%, protein content of 9.191%, texture of 0.088 mm / gr.dtk and organoleptic value by the number of 149 flavor rank, color of 125.5.and texture of 147.5Key words : Tofu, Cowpea, citric acid